SMEs capital structure determinants: empirical evidence from Kazakhstan - Kokeyeva, Samal (Uwarunkowania struktury kapitału MŚP na przykładzie spółek z Kazachstanu, 2019)
The purpose of this paper is to study the standard firm-factor determinants on capital structure of small and medium-sized enterprises (SMEs). To this end, we analyzed small and medium sized firms in Kazakhstan, where all sectors were considered. We use panel data methods to investigate the determinants of capital structure for non-financial SMEs in Kazakhstan. This study examines the impact of key determinants such as asset tangibility, size, growth, profitability and tax rate of SMEs. The trade-off theory and the pecking order theory of capital structure guided this study. The results suggest that despite some differences in the influence of factors on the capital structure, most of the determinants presented by the theory of finance appear indeed to be relevant for the Kazakhstan small and medium business sector
Financial Sciences. Nauki o Finansach, 2019, vol. 24, no. 3, s. 13-22
Keywords: capital structure; panel data; SMEs; struktura kapitału; dane panelowe; MŚP